Determination of natural radionuclides in waste generated in the potable water treatment plants of the Zona da Mata of the state of Pernambuco- Brazil - Adriana Muniz de Almeida Albuquerque (Brazilian Journal of Radiation Sciences, 2019)
The water purification procedure aims to obtain a product appropriate for human consumption, minimizing the presence of contaminants and toxic substances present in the water. Among these contaminants, some radionuclides of natural origin, such as uranium, thorium and their descendants, have been identified. Studies have shown that the stages of purification are quite effective in removing the radionuclides contained in water. The removal is due to co-precipitation of the radionuclides with the suspended materials and the precipitated material is accumulated and characterized as a Technologically Concentrated Natural Occurrence Radioactive Material (TENORM) by the United States Environmental Protection Agency (USEPA). This residue can present significant levels of radioactivity and, when discarded in the environment without any treatment, can generate a problem of environmental impact and a risk to the health of the population. In this way, some gamma emitters of the series of U, Th and the K-40 were determined in the residues generated at the Potable Water Treatment Plants – PWTPs in six municipalities of Pernambuco. The results obtain corroborate the classification of the residues generated in the PWTPs as concentrators of the radioactive components contained in the water supplied to the system and reinforce the need for the release to the environment, which is the usual way of disposal of this waste, to be carried out only after considering the radiological protection standards established.